The Development of Natural Tourism of Pine Forest in Kidang Pananjung Village, Cililin District, West Bandung Regency - Eldo Delamontano; Reiza D Dienaputra; Cecep Ucu Rakhman (Jurnal Penelitian Kehutanan BONITA, 2024)
The Indonesian government's efforts to improve village development can be seen in the Developing Village Index (IDM). All village potential needs to be looked at carefully by the village government and then managed sustainably. This research aims to utilize Google Maps reviews on natural tourism potential in the village. It is hoped that the approach of using Google Maps reviews can be carried out by village governments in general in Indonesia. The results of qualitative descriptive analysis can be used as a basis for ideas for village development and development through tourism destinations in the village. This research was conducted at Wisata Pinus Pananjung, a natural tourist attraction in Kidang Pananjung Village, Cililin District, West Bandung Regency, West Java. The results of the research are the need to form a sports and arts and culture community with regular activities that utilize the Wisata Pinus Pananjung area. Community activities require the participation of the community and village government. Community activities also increase trade activities with potential visitors coming from inside and outside the village. This requires a touch of digital marketing including the use of Google Maps. This idea is in line with the priority of Kidang Pananjung Village in IDM 2023 to become a Desa Maju.